Organisational Transformation and Scientific Change : the impact of institutional restructuring on universities and intellectual innovation. - Whitley, Richard (Research in the sociology of organizations., 2014)
The first part of this book deals with the transformation of universities as strategic organisational actors - in some cases creating them as such - while the second shows how governance and authority shifts are affecting the kinds of research goals being pursued by academics in different public science systems.